Determination of eutrophication potential of particles in rivers and waterbody sediments - Jan, Jiří (Jihočeská univerzita, 2016)
Extraction solutions were assessed to find the most appropriate method for characterisation of particles in the context of release or uptake phosphorus in non-calcareous regions. Advantages and limitations of methods for determination of different phosphorus (P) forms and its important binding components iron and aluminium (hydr)oxides, were pointed out. Characterisations of these forms, that show highly different behaviour under changing environmental conditions, were used for the assessment of particles saturation with respect to P. Sorption/desorption behaviour of soil particles susceptible to erosion and their content of plant available P was tested. Strong correlation, which is dependent on P saturation ratio, was used to propose a method for the determination of soil erosion impact to supply dissolved P in stream waters of variable dissolved P concentration.
Determination of eutrophication potential of particles in rivers and waterbody sediments
Keywords: phosphorus; iron; aluminium; eutrophication potential; sorption; particles; sediment; fractionation; extraction; Mehlich 3; phosphorus; iron; aluminium; eutrophication potential; sorption; particles; sediment; fractionation; extraction; Mehlich 3